Impact of Dividend Policy Analysis on Fluctuations in Stock Price of Food and Beverage Companies - Ade Onny Siagian; Ninuk Riesmiyantiningtias; Rizky Amalia (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2022)
This study aims to determine the effect of dividend policy on stock prices in food and beverage companies listed on the Indonesia Stock Exchange. The results of the research of PT Sekar Laut, from the results of the calculation of the correlation analysis obtained the value of the coefficient = 0.33 which means that it has a very weak relationship or there is no relationship between dividend policy and stock price movements and the coefficient of determination is 10.89%, which means the effect of dividend policy on stock price fluctuation was only 10.89%, the remaining 89.11% was caused by other factors and for PT. Ultra Jaya, from the results of the calculation of the correlation analysis obtained the coefficient of determination 0.96, meaning that dividends per share have a strong relationship with stock price movements, and the coefficient of determination is 92.16%, which means that the effect of dividend policy on stock price fluctuations is 92.16%, the rest is 92.16%. 7.84% caused by other factors, as well as for PT. Ades Alfindo Putra Setia, from the results of the calculation of the correlation analysis obtained a coefficient of 0.86 (the value of r is close to a positive and strong number) with a determination coefficient of 73.96%, then the effect of dividend policy on stock price fluctuations is 73.96%, the remaining 26.04% caused by other factors. The value of 96 (the value of r is close to one) means that dividend per share has a strong relationship with stock price movements, and the coefficient of determination is 92.16%, which means that the effect of dividend policy on stock price fluctuations is 92.16% and the remaining 7.84% is caused by factors